Impact of oil price shocks on the economies of rentier countries - an econometric study on a sample of OPEC countries - nadir, abderrazak; benmohad, Samir (Journal of Research in Finance and Accounting, 2022)
We aim through this paper to try to determine the economic effects of oil price shocks (continuously rising oil prices) in rentier countries (which depend heavily on oil revenues), by estimating the impact of price shocks on some macroeconomic indicators, namely income, budget deficit and inflation rate. We found that the impact of oil price shocks on the mentioned indicators differs at the two levels, the panel data, where a positive shock in oil prices had a positive effect on both income and the budget balance, and a negative effect on the inflation rate. And at the individual level (Time Series), where the nature of (response to positive shock on oil prices) and the intensity (the ratio of the impact of price fluctuations on the situational fluctuations of the study variables) differ between different sample countries, using VAR models.